Stomach cancer incidence in Southern Portugal 1998-2006:a spatio-temporal analysis - Papoila, Ana Luisa (2012)
Understanding geographical differences in health, particularly in small areas, became a major concern of epidemiologists. Geographical association studies and, more recently, several spatial disease mapping studies have emerged due to the development of new spatial statistical tools. Among other diseases, these methods are being applied to analyze cancer data. However, in this kind of studies, it is of utmost importance to also investigate the influence of temporal variability and that is why spatio-temporal studies became so popular. The aim of this study is to investigate spatial and temporal trends for the incidence of this type of cancer. This retrospective population-based study is based on data on all stomach cancers registered by the Southern Portuguese Cancer Registry (ROR Sul) between 1998 and 2006. Because several studies have underlined the important role of socioeconomic status in cancer risk, information on this variable has also been taken into account. Bayesian hierarchical models were applied to model stomach incidence at a county level and resulting relative risks were used to build risk maps for cancer incidence. Age-Period-Cohort models were also applied.